A family of octapamine receptors that specifically induce cyclic AMP production or Ca2+ release in Drosophila melanogaster - Balfanz, Sabine; Frings, Stephan (Journal of neurochemistry, 2005)
In invertebrates, the biogenic-amine octopamine is an important physiological regulator. It controls and modulates neuronal development, circadian rhythm, locomotion, ‘fight or flight’ responses, as well as learning and memory. Octopamine mediates its effects by activation of different GTP-binding protein (G protein)-coupled receptor types, which induce either cAMP production or Ca2+ release. Here we describe the functional characterization of two genes from Drosophila melanogaster that encode three octopamine receptors. The first gene (Dmoa1) codes for two polypeptides that are generated by alternative splicing. When heterologously expressed, both receptors cause oscillatory increases of the intracellular Ca2+ concentration in response to applying nanomolar concentrations of octopamine. The second gene (Dmoa2) codes for a receptor that specifically activates adenylate cyclase and causes a rise of intracellular cAMP with an EC50 of ∼3 × 10−8 m octopamine. Tyramine, the precursor of octopamine biosynthesis, activates all three receptors at ≥100-fold higher concentrations, whereas dopamine and serotonin are non-effective. Developmental expression of Dmoa genes was assessed by RT-PCR. Overlapping but not identical expression patterns were observed for the individual transcripts. The genes characterized in this report encode unique receptors that display signature properties of native octopamine receptors.